Incapacity in childbirth - Rare or common? - Neelam Singh; Peter Lepping; Rhiannon Whitaker; Barkat Masood; Shweta Joshi; Philip Banfield (Elsevier, 2021)
Objective: Impaired decision making ability is common on general medical wards. Audit evidence suggests that the prevalence of incapacity may be higher than previously assumed in Obstetric Emergency Procedures (OEP) during childbirth. We investigated the prevalence of incapacity in OEP and factors associated with this. Design: Capacity to consent to treatment was assessed retrospectively in 93 women undergoing OEP. All women were interviewed using a semi-structured questionnaire aided interview within 24 h of the emergency. Five assessors (3 obstetricians and 2 psychiatrists) were asked to determine capacity to consent from audio recordings of the interviews. Results: All 5 assessors determined 59 % of women to have capacity to consent to treatment and 2 % of women to lack capacity. In 39 % of women there was some disagreement between assessors. Using a majority decision (3 assessors in agreement), 14 % of women lacked capacity. High pain scores, young age and no previous history of theatre deliveries were associated with more incapacity judgments, whilst parity and history of mental illness were not. Using a 7point Likert scale only marginally improved agreement between assessors, compared to their binary decision. Conclusion: It is often assumed that it is rare to lack capacity in an obstetric emergency procedure during childbirth, but these data suggest that incapacity may be relatively common. In particular, severe pain is a demonstrable risk factor for impaired capacity. Wide variation between assessors questions the validity of current commonly employed (informal) methods used in clinical practice to assess capacity to consent during OEP.